2014
DOI: 10.1016/j.electacta.2014.05.163
|View full text |Cite
|
Sign up to set email alerts
|

Zr-based conversion layer on Zn-Al-Mg alloy coated steel sheets: insights into the formation mechanism

Abstract: Zr-based conversion layers are considered as environmentally friendly alternatives replacing trication phosphatation in the automotive industry. Based on excellent electronic barrier properties they provide an effective corrosion protection of the metallic substrate. In this work, thin protective layers were grown on novel Zn-Al-Mg alloy coated steel sheets by increasing the local pH-value at the sample surface leading to deposition of a Zr-based conversion layer. For this purpose Zn-Al-Mg alloy (ZM) coated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 40 publications
1
44
0
Order By: Relevance
“…Mechanical pre-treatment in the form of grinding and/or polishing may precede chemical pre-treatment but chemical pre-treatment is often applied without prior mechanical treatment. In some cases, the surface was not mechanically pre-treated but cleaned with ethanol 102 or acetone, 55 For rinsing, deionized water is usually used, although also tap water 92,94,106,112 was applied to make the procedure simpler for industrial processing. Due to environmental and health concerns related to toxicity and carcinogenicity of chromates, procedures that reduce the worker exposure and discharge into the environment were introduced.…”
Section: Effect Of Substrate On Coating Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical pre-treatment in the form of grinding and/or polishing may precede chemical pre-treatment but chemical pre-treatment is often applied without prior mechanical treatment. In some cases, the surface was not mechanically pre-treated but cleaned with ethanol 102 or acetone, 55 For rinsing, deionized water is usually used, although also tap water 92,94,106,112 was applied to make the procedure simpler for industrial processing. Due to environmental and health concerns related to toxicity and carcinogenicity of chromates, procedures that reduce the worker exposure and discharge into the environment were introduced.…”
Section: Effect Of Substrate On Coating Formationmentioning
confidence: 99%
“…33,34,36,37,47,51,52,55,59,61,62,[64][65][66]69,70,72,78,82,84,87,90,92,94,95,98,99,101,102,104,[106][107][108]110,[112][113][114] Elevated temperatures were also studied, i.e. between 30 and 55…”
mentioning
confidence: 99%
“…In such coatings, it has been shown that copper from the pre‐treatment bath preferentially deposits on the intermetallic particles rich in Fe and Si on AA6014 . Surface‐element distribution also determines deposition of ZrO 2 ‐based conversion coatings on Zn–Al–Mg surfaces of metallic coatings . A larger hydroxyl fraction on the base material enhances the deposition of ZrO 2 ‐based conversion coatings, as shown by a greater thickness on AA6014, and a detailed in situ mechanistic study on zinc oxide .…”
Section: Introductionmentioning
confidence: 99%
“…During the last 30 years, Zn-Al-Mg alloys have attracted worldwide attention due to their excellent mechanical and corrosion resistance properties as sacrificial coatings to substitute traditional Zn coating for the protection of steel structures [1][2][3][4]. Zn-Al-Mg alloys can also be used in light metal structures due to their advantages such as low-density, high-strength to weight ratio and high-specific toughness.…”
Section: Introductionmentioning
confidence: 99%